SISTEM PENDUKUNG KEPUTUSAN PENENTUAN LOKASI PENDISTRIBUSIAN ROTI TERBAIK PADA ZUHRO BAKERY MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Cahya, Ananda Putri; Sulindawaty, Sulindawaty (Majalah Ilmiah Kaputama, 2020)
Distribution location is very influential on the ups and downs of sales at Zuhro Bakery because the company distributes its bread to wholesalers and stalls so that sales are not only through mobile vendors by distributing bread to wholesalers and stalls, sales at Zuhro Bakery will be more widespread and will be more numerous people who know the bread produced from Zuhro Bakery. However, some locations are always crowded with buyers or lonely buyers. Therefore a decision support system was designed to determine the location of the best bread distribution in Zuhro Bakery using the simple additive weighting method. This research was conducted to make it easier for Zuhro Bakery to prioritize the best distribution locations to increase sales at Zuhro Bakery. The Simple Additive Weighting (SAW) method is one of the methods known as the weighted sum method. The SAW method looks for the best alternative for all attributes with weighted sums. Then the results obtained from this decision support system in determining the location of the best bread distribution based on the calculation results with the highest-ranking value using the SAW method is an A2 alternative, namely Wholesale 2 = 2.68.